P.79: WITHDRAWN: P.80: Analysis Commentary of Polymer Network Structure of Polymer Stabilized Blue Phase. Issue 1 (1st July 2013) - Kwak, Musun; Jeon, Jongho; An, Sangjin; Kim, Kyoungri; Yi, Yoonseon; Choi, Seungkyu; Kim, Nakwon; Kim, Byungjae; Kang, Dongwoo; Choi, Youngseok; Jeon, Suho
Abstract After removing liquid crystals (LCs) using hexane cleansing solution, polymer network (PN) structure of polymer stabilized blue phase (PSBP) was analyzed. PN type had different shape in the surface region (nearby glass) and intermediate region. Directly measured PN structure and theoretical polymer line defect on the cubic symmetry were compared. Moreover, analysis of different kind of LC and monomer, PN appeared in membrane state.